Порівняння в міжмовній комунікації (на матеріалі німецькомовних перекладів Вільгельма Горошовського) - Матвіїшин, Оксана Миколаївна; Matviyishyn, O. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті схарактеризовано порівняння як засіб вираження етнокультурних особливостей і національної ментальності українського та німецькомовного народів. З огляду на образність порівняння, актуальним є дослідження особливостей його відтворення німецькою мовою в перекладах В. Горошовського. На основі зіставного аналізу першотвору й перекладу продемонстровано способи відтворення порівнянь цільовою мо¬вою, які визначають рівень адекватності перекладів В. Горошовського. Крім дослівного способу, домінують ампліфікації, опущення й еквівалентні відповідники українським порівнянням. The article deals with the simile as a means of expressing ethnic and cultural peculiarities and national mentality of the Ukrainian and German peoples. Taking into consideration the figurativeness of the simile it is topical to research the peculiarities of its rendering into German in V. Horoshovskyi’s translations. On the basis of the contrastive analysis and translation of the original we have demonstrated the ways of rendering similes into the target language that determine the level of adequacy of V. Horoshovskyi’s translations. Apart from word-for-word translation amplification, omission and equivalents of Ukrainian similes predominate in his translations. Linguo-stylistic and translation analysis showed that the translation of similes is connected with rendering their semantics, image and functions which they perform in fiction. Lexical and grammatical means of expressing similes also show convergent and divergent features due to the fact that German and Ukrainian belong to different language types. When translating comparative constructions one should take into consideration their logical subject-matter, expressive and emotional, stylistic and functional characteristics, as well as preserving traditionalism and the use of the expression.
The Simile of Interlanguage Communication (Based on German Translations by V. Horoshovskyi)
Keywords: порівняння; simile; художній переклад; literary translation; перекладацькі трансформації; translation procedures